Detecting indoor positioning of moving object using wifi triangulation algorithm for kid tracker application - Wan Nor Afiqah, Wan Othman (2016)
The increasing number of missing kid from days to days is become main concern for parents. Hence, „Detecting Indoor Positioning of Moving Object using Wi-Fi Triangulation Algorithm for Kid Tracker Application‟ as a part of process in Kid Tracker Application to keep track our kids movement by focusing inside the building (shopping mall). It will use Wi-Fi technology with the integration of smartphone capability to recognise our kids‟ position which will display it on smartphone. Based on the research, there are few similar applications on the market, but mostly developed for outdoor environment using GPS technology. Because of GPS signal based on satellite which created for outdoor environment, it does not fit for indoor environment. In addition, most of them are provide limited location accuracies range. Overall, this proposed system is a part of process in Kid Tracker Application in order to get kid position in indoor environment. The main objective for this research is to calculate the position of the object based on the distance using Wi-Fi Triangulation Algorithm. Others are to obtain the significant distance of the object by using three Wi-Fi access points and to assess the position of movement object in real time. Hence, this research focuses for indoor positioning and the searching range will cover for one level. Besides that, the Wi-Fi will cover up to 20 meters inside the building and use Wi-Fi signal strength which is Level and Frequency to collect the data and to determine the location detection. Agile Methodology is used in developing this system to get better quality of final system. As a result, this application can detects real time kids‟ position with acceptable time but not in accuracy due to some signal problem of Wi-Fi access point.